A study of the changes of some chemical components of different models Rainbow trout preserved by freezing - أحمد, سحر; علي عياش,; سمر حسن ,; علي عثمان , (Latakia University Journal -Biological Sciences Series, 2023)
The study has aimed to choose the best model for preserving rainbow fish (Trout) by freezing, where the following forms are preserved: S1 A sample of Ungutted fish S2 A Sample of gutted fish S3 A sample of fish fillets divided longitudinally into two symmetrical longitudinal fillets not separated from each other. The S3 model was characterized by more preservation of the sensory properties and chemical components, as the percentages at the end of the S1 model freezing:( protein 15%, Lipid 7%, volatile nitrogen 0.33%, peroxide number 0.61), where the percentages at the end of freezing for model S2 were: (protein 17%, Lipid 7.8%, , volatile nitrogen 0.33%, peroxide number 0.61),while the percentages at the end of freezing for the S3 model ( protein 15%, Lipid 8.5%, volatile nitrogen 0.33%, peroxide number ( 0.61 It was found that the S3 model is superior to the other two models with its ability to preserve the chemical components. This model can be frozen for a period of 180 days, while the freezing period preferred for the other two models is 120 days.